Flux Growth of Single-Crystalline Hollandite-Type Potassium Ferrotitanate Microrods From KCl Flux - Hayashi, Fumitaka; Furui, Kenta; Shiiba, Hiromasa; Yubuta, Kunio; Sudare, Tomohito; Terashima, Chiaki; Teshima, Katsuya (Frontiers in Chemistry, 2020)
Hollandite-type crystals have unique and interesting physical and chemical properties. Here, we report the flux growth of hollandite-type single-crystalline potassium ferrotitanate (KFTO) with faceted surface features from a KCl flux. We varied the flux growth conditions, including the kind of flux, holding temperature, and solute concentration for growing faceted crystallites. KCl was found to be the best flux to grow the single-crystalline KFTO particles, while heating at or above 900 °C was needed to yield the KFTO single crystals. The crystal growth was only weakly dependent on the solute concentration. Next, we characterized the grown single crystals and discussed the manner of their growth from the KCl flux. TEM images with clear electron diffraction spots indicated that the KFTO crystals grew along the <001> direction to form microrods ~10 µm in size. DFT calculation results indicated that the surface energy of the (100) face is higher than that of the (001) face. Based on these characterization results, we proposed a possible growth mechanism of the KFTO crystals.